The Association between Antiphospholipid Syndrome after Conventional Treatment and Preeclampsia - Tian Yang; Hongling Peng (Clinical and Experimental Obstetrics & Gynecology)
Background: Despite conventional treatment, the prognosis of antiphospholipid syndrome (APS) pregnancy remains poor, and some pregnancies are still complicated by preeclampsia (PE). This study aimed to identify the relationship between conventionally-treated APS and the onset of PE. Methods: Relevant studies published up to April 2021 were searched on the PubMed, Cochrane Library, and Embase databases. Related data were extracted from the included studies, and we performed a meta-analysis. Review Manager 5.4 were used to calculate the pooled odds ratio (OR) and 95% confidence intervals (CIs). Results: This study screened 6 studies, including 1 cohort study and 5 case-control studies. Even after conventional treatment, the rate of PE in APS pregnancy is still significantly higher than in the control group. There was a higher pooled OR in the cohort study (OR: 8.37, 95% CI: 3.42–20.48) than the case-control studies (OR: 2.30, 95% CI: 1.12–4.74) in the subgroup analysis. Conclusions: APS pregnancy increases the risk of PE even after conventional treatment. Routine monitoring and standardized and better treatment methods should be developed to prevent the occurrence of PE.